2003
DOI: 10.1115/1.1602478
|View full text |Cite
|
Sign up to set email alerts
|

Local Heat Transfer Characteristics in Simulated Electronic Modules

Abstract: When heat is released by forced convection from electronic modules in a narrow printed circuit board channel, complex flow phenomena—such as stagnation and acceleration on the front surface, separation and reattachment on the top surface, wake or cavity flow near the rear surface—affect the heat transfer characteristics. The purpose of this study is to investigate how these flow conditions influence the local heat transfer from electronic modules. Experiments are performed on a three-dimensional array of hexah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Their results show that the installation of an inclined plate above an upstream source results in a periodically unsteady flow and enhances the heat transfer performance. Yoo et al [28] investigated local turbulent heat transfer characteristics in simulated electronic modules with and without vortex generator experimentally, and the rectangular wing type vortex generator has been found to be more effective than the delta wing type vortex generator. In Fu and Tong's [29] two-dimensional, incompressible, and laminar air flow study, a numerical simulation was performed to study the influence of an oscillating cylinder on the heat transfer from heated blocks in a channel flow.…”
Section: Introductionmentioning
confidence: 99%
“…Their results show that the installation of an inclined plate above an upstream source results in a periodically unsteady flow and enhances the heat transfer performance. Yoo et al [28] investigated local turbulent heat transfer characteristics in simulated electronic modules with and without vortex generator experimentally, and the rectangular wing type vortex generator has been found to be more effective than the delta wing type vortex generator. In Fu and Tong's [29] two-dimensional, incompressible, and laminar air flow study, a numerical simulation was performed to study the influence of an oscillating cylinder on the heat transfer from heated blocks in a channel flow.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that thermal insulation of the cavity could be achieved through the use of high velocity horizontal flow. Local heat transfer characteristics in electronics modules were studied by Yoo et al (2003). They indicated that longitudinal vortices formed by vortex generator enhanced the mixing of fluids and thereby heat transfer, and the rectangular wing type vortex generator was found to be more effective that the delta wing type vortex generator.…”
Section: Introductionmentioning
confidence: 99%
“…by Yoo et al[27] in the Reynolds number range of 1.29 x 10 4 to 3.87xl0 4 (based on channel height) has examined the local heat transfer coefficient in both two-dimensional and three-dimensional module arrays. The two-dimensional module array data showed a little lower value than the three-dimensional results, as a result of bypass flow.…”
mentioning
confidence: 99%